The influence of agricultural land‐use on plant and macroinvertebrate communities in springs. (26th November 2015) - Knysh, Kyle M.; Giberson, Donna J.; van den Heuvel, Michael R.
Abstract: Many freshwater cool springs can be characterized by nearly constant temperatures and chemical composition. Agricultural activities may leach nutrients to the groundwater, add sediment and nutrients from overland flow, and change the cover of the riparian area surrounding springs, all factors that influence aquatic invertebrate and plant communities. Twenty limnocrene springs in Prince Edward Island, Canada (10 surrounded by and within 20 m of agricultural land, and 10 located in forested areas with < 5% agriculture within 1 km) were studied to determine effects of agricultural activities on invertebrate and plant community structure. Chemical, flow, sediment, and cover variables were examined in all 20 springs, and invertebrates and macrophytes were evaluated in a subset of four agricultural and four forested springs. Although nutrients (particularly nitrate) were higher in agricultural springs than in forested ones, and plant communities differed between springs in the two land use types, light level (relating to the riparian canopy in the two land‐use types) was a stronger predictor of aquatic plant community composition than nutrients. Plant diversity was highest in open agricultural sites. Overall invertebrate richness and abundance were higher in forested sites than agricultural sites, but invertebrate community composition differed between the two land‐use types, and was primarily related to aquatic plant composition. Few taxa responded directly to elevated nutrients. The composition of the riparian area may be more important than direct inputs of nutrients and sedimentation when assessing agricultural impacts on springs.